2007
DOI: 10.1111/j.1742-1241.2007.01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation for pulmonary hypertension

Abstract: Lung transplantation is an accepted therapeutic intervention for patients with pulmonary arterial hypertension (PAH) who fail medical therapy. Highly selected candidates with PAH may enjoy improved survival by combining medical therapy with transplantation. Despite the known benefits of lung transplantation that include improvement in haemodynamics, exercise tolerance, shortness of breath and long-term survival, this intervention is associated with significant shortcomings. These include, the need for lifelong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Most experts believe pulmonary vascular disease at the time of LT (IPAH or secondary PAH) to be a risk factor for PGD. 134 Animal studies using SLT in rats for chemical-induced PAH demonstrate a preferential flow of blood to the allograft that was fatal in cases of severe preoperative PAH, presumably because of PGD-related complications. 135,136 A retrospective review in humans comparing SLT for PAH versus emphysema confirmed significantly increased allograft blood flow in the PAH patients.…”
Section: Ipah and Primary Graft Dysfunctionmentioning
confidence: 99%
“…Most experts believe pulmonary vascular disease at the time of LT (IPAH or secondary PAH) to be a risk factor for PGD. 134 Animal studies using SLT in rats for chemical-induced PAH demonstrate a preferential flow of blood to the allograft that was fatal in cases of severe preoperative PAH, presumably because of PGD-related complications. 135,136 A retrospective review in humans comparing SLT for PAH versus emphysema confirmed significantly increased allograft blood flow in the PAH patients.…”
Section: Ipah and Primary Graft Dysfunctionmentioning
confidence: 99%
“…When disease progresses on maximal therapy, lung transplantation, for those who qualify, remains a viable option. Orens (19) in this edition describes its crucial role for advanced PH. The issues of specialised care for these complex patients are addressed by Housten‐Harris (20).…”
Section: This Edition Of Reviewsmentioning
confidence: 99%